Aedes aegypti L. Controlling based on Lethal MosquitoTRAP Modification (LMM) in Mataram City - Sazalia, Munawir; Soesilohadia, RC Hidayat; Wijayantia, Nastiti; Wibawa, Tri (Proceeding International Conference on Science and Engineering, 2020)
Dengue hemorrhagic fever is a global public health problem that caused an Arbovirus. Mataram city was a high infected area in West Nusa Tenggara Province, which included six sub-districts. The objective of this study is monitoring and controling dengue virus vectors based on temporal patterns using mosquitoTRAP. This research was explanatory in the cross-section design in 102 households (indoor and outdoor) as an observation site. Based on mosquito collection in October 2018 until March 2019, the amount reached 2,396 mosquitos such as Aedes albopictus (41%) and Aedes aegypti (59%). The mosquitos collection based on observation site showed no significant difference number (P=0.863). However, the number of mosquitos in temporal pattern showed significant difference number of first, middle, and end rain season (P = 0.001). Mosquitoes population at rain season had shown an increase until March 2019. Therefore, monitoring and controlling Aedes mosquitoes is crucial for prevention of dengue hemorrhagic fever case.